Three Aspects of Information Science in Reality: Symmetry, Semiotics and Society - Joseph E. Brenner (Information, 2015)
The 2nd International Conference on the Philosophy of Information (ICPI 2015) took place in Vienna June 5–6, 2015 as a major Section of the Vienna 2015 Summit Conference on the Response and Responsibility of the Information Sciences. At the ICPI, Wu Kun and others presented evidence for a current integration and convergence of the philosophy and science of information, under the influence of the unique characteristics of information itself. As I have shown, my extension of logic to real systems (Logic in Reality; LIR) applies to and explicates many of the properties of information processes. In this paper, I apply LIR as a framework for understanding the operation of information in three areas of science and philosophy that were discussed at the Summit. The utility of this approach in support of an information commons is suggested the abstract section.